The Effect of ESG Disclosure, Manager Qualification and Workplace Safety on Firm Value with Firm Size and Financial Leverage as Control Variables In Manufacturing Companies Listed on the Indonesia Stock Exchange year 2020-2022 - Sumiati Sunarsih,; Yvonne Augustine, (Technium Sustainability, 2024)
The purpose of this study, which was designed with firm size and financial leverage acting as control variables, was to ascertain the impact of management qualification, workplace safety, and ESG disclosure on firm value as estimated by Tobin's Q. Manufacturers (mining, metal, and cement) that are listed on the IDX in 2020–2022 make up the study's community. This study employed multiple linear regression-ordinary least squares along with hypothesis testing, where the regression coefficient is tested using the t test. The findings show that Manager Qualification (MQ) has a significant positive impact on Firm Value (FV), Financial Leverage (FL) has a substantial negative impact on Firm Value (FV). While ESG disclosure, Workplace Safety (WS) and Firm Size (FS) have no substantial influence on Firm Value (FV). The variable that has the highest significant level (0.008 < 0.005) but the coefficient is negative is Financial Leverage (FL) due to the calculated t value of -2.71, followed by the Manager Qualification (MQ) variable with a significant level (0.023 < 0.05) with a positive coefficient. And followed by the Firm Size (FS) variable, the Workplace Safety (WS) variable, and ESG disclosure does not have a substantial impact because the coefficient value obtained is 0.116; 0.196; and 0.451, respectively, where the coefficient value is higher than 0.05. The outcomes demonstrated that Firm Value (FV) increases along with the increase in Manager Qualification (MQ) and Financial Leverage (FL) has a substantial negative impact on Firm Value (FV). While Firm Size (FS), Workplace Safety (WS), and ESG disclosure variables have no significant effect.